Implementasi Konsep Time Capsule dalam Perancangan Interior Planning Gallery of Surabaya - Melissa Ardani; Diana Thamrin; Linggajaya Suryanata (Intra, 2019)
Surabaya is the second largest city in Indonesia right after Jakarta, the capital. It has a myriad of achievements, one of which is the implementation of their open government system. The interior design of planning gallery of Surabaya is a response to that Open Government award from Singapore magazine by enhancing the Open Government system. Surabaya is yet to have a place where people can get information on city planning, which could create a transparency between the people and the government. The gallery could also be an educational center where people can participate and keep track of the city’s development. The methods used in the design is design thinking, consisting of seven steps: sense intent, know context, know people, frame insight, explore concepts, frame solutions, dan realize offering. The result is a gallery with the concept of a time capsule that holds the city’s past and future. The design has a galery with an exhibition hall, a theater, a communal room, maquette area, cafe, an aspiration room, and consultation area. At the exhibition hall, people can get information on Surabaya’s present, like facts & challenges that the city is currently facing, and on Surabaya’s future where people can contribute to the city’s development. This gallery could be a space where the people can learn, address their aspiration, and discuss the development of Surabaya.